Health Branding Ethics - Anker, Thomas Boysen; Sandøe, Peter 1955-; Kamin, Tanja; Kappel, Klemens (2011)
Commercial food health branding is a challenging branch of marketing because it might, at the same time, promote healthy living and be commercially viable. However, the power to influence individuals’ health behavior and overall health status makes it crucial for marketing professionals to take into account the ethical dimensions of health branding: this article presents a conceptual analysis of potential ethical problems in health branding. The analysis focuses on ethical concerns related to the application of three health brand elements (functional claims, process claims, and health symbols) as well as a number of general concerns that apply to health branding as such. Being a pioneering analysis, this article advances the academic understanding of health branding and provides practitioners with knowledge of important concerns to take into account when marketing health brands.
Keywords: Medicalization; Stereotyping; Pathologizing; Exploitation of false inferences; Distortion of health knowledge; Inducement of false beliefs; Health symbols; Process claims; Health claims; Health branding ethics